Computer graphics as an enabling technology for cooperative, global applications - Marcos, Adérito (2011)
In this article I would like to highlight one of the research and technological areas receiving considerable influence from CG technology, namely the computer-supported cooperative work (CSCW) environments. A report on some representative projects and applications in this area is also presented.